Late Roman to late Byzantine/early Islamic period lamps in the Holy Land : the collection of the Israel Antiquities Authority - Sussman, Varda, (Archaeopress archaeology., 2017)
This volume illustrates lamps from the Byzantine period excavated in the Holy Land and demonstrates the extent of their development since the first enclosing/capturing of light (fire) within a portable man-made vessel.